VD_FINDINFO Pron / 2014 / 42 vom 18. Juni 2014 - VD Tribunal cantonal (2014)
DÉCISION SUR FRAIS, PROTECTION DE L'UNION CONJUGALE, TRANSACTION JUDICIAIRE | 109 al. 1 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)